Loneliness as a mediation from social support leading to a decrease of health-related quality of life among PLWHIV - Qian, Zhe; Li, Bing; Liao, Leyi; Liao, Guichan; Chen, Hongjie; Han, Juanqing; Yu, Tao; Xu, Xuwen; Peng, Jie; Cai, Shaohang (Frontiers in Public Health, 2023)
This study focused on the mental health of people living with HIV(PLWHIV) and explored their relationship between loneliness and perceived social support, health related quality of life (HRQoL) with a method of structural equation model. We collected clinical and psychological data from consecutively enrolled PLWHIV. A total of 201 PLWHIVs were enrolled and measured with self-reporting survey instruments of UCLA Loneliness Scale, Self-Rating Depression Scale, Self-Rating Anxiety Scale, Social Support Ratio Scale and Short Form Health Survey-36. The levels of loneliness, depression, anxiety, perceived social support and HRQoL were assessed. PLWHIV enrolled were divided into two groups of loneliness and non-loneliness based on their UCLA Loneliness Scale scores. Multivariable analysis indicated that being married is a protective factor associated with loneliness (OR=0.226; P=0.032). We further found the loneliness group had a higher level of depression (P<0.001) and anxiety (P<0.001), but lower level of HRQoL (P<0.001) than the non-loneliness group. We found there was a positive linear correlation between social support and HRQoL among the enrolled PLWHIVs (r2=0.059; P=0.0005). A structural equation model (SEM) was established to evaluate whether the loneliness played as a mediation role between social support and HRQoL. The model showed loneliness as a mediation from social support leading to a decrease of HRQoL. Our findings showed a potential psychological pathway from social support to HRQoL, suggesting the need for interventions focusing on social support may improve poor HRQoL lead by loneliness.